COVID-19 and Courts: An Exploration of the Impacts of the Pandemic on Case Processing and Operations - Viglione, Jill (Victims & offenders, 2023)
The COVID-19 pandemic instantly changed the day-to-day practices of the criminal justice system. The court system, traditionally reliant on face-to-face interaction, had to quickly alter operations to decrease the virus’ spread while remaining functional as an integral role in the criminal justice system. The current exploratory study examines the response strategies U.S. court systems implemented, impacts on case processing, case backlogs, and additional consequences endured due to the pandemic. Using responses from self-report surveys of court staff (e.g., judges, clerks), results indicated that courts prioritized the types of cases heard and implemented multiple mitigation strategies that were deemed effective, some of which may be sustainable post-pandemic. Despite an increase in virtual jury trials and hearings, many courts saw a surge in backlogged cases and complications in assembling juries. The overall findings may inform judiciary policy and practice concerning short and long-term pandemic outcomes on court processing and future pandemic preparedness.